Biocompatibility and bioactivity of calcium silicate-based endodontic sealers in human dental pulp cells - Mestieri, Leticia Boldrin [UNESP]; Gomes-Cornelio, Ana Livia [UNESP]; Rodrigues, Elisandra Marcia [UNESP]; Salles, Loise Pedrosa; Bosso-Martelo, Roberta [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Tanomaru-Filho, Mario [UNESP] (Univ Sao Paulo Fac Odontologia Bauru, 2015)
Mineral Trioxide Aggregate (MTA) is a calcium silicate-based material. New sealers have been developed based on calcium silicate as MTA Fillapex and MTA Plus. Objective: The aim of this study was to evaluate biocompatibility and bioactivity of these two calcium silicate-based sealers in culture of human dental pulp cells (hDPCs). Material and Methods: The cells were isolated from third molars extracted from a 16-year-old patient. Pulp tissue was sectioned into fragments with approximately 1 mm(3) and kept in supplemented medium to obtain hDPCs adherent cultures. Cell characterization assays were performed to prove the osteogenic potential. The evaluated materials were: MTA Plus (MTAP); MTA Fillapex (MTAF) and FillCanal (FC). Biocompatibility was evaluated with MTT and Neutral Red (NR) assays, after hDPCs exposure for 24 h to different dilutions of each sealer extract (1: 2, 1: 3 and 1: 4). Unexposed cells were the positive control (CT). Bioactivity was assessed by alkaline phosphatase (ALP) enzymatic assay in cells exposed for one and three days to sealer extracts (1: 4 dilution). All data were analyzed by ANO A and Tukey post-test (p <= 0.05%). Results: MTT and NR results showed suitable cell viability rates for MTAP at all dilutions (-13). Cells exposed to MTAF and FC (1: 2 and 1: 4 dilutions) showed significant low viability rate when compared to CT in MTT. The NR results demonstrated cell viability for all materials tested. In MTAP group, the cells ALP activity was similar to CT in one and three days of exposure to the material. MTAF and FC groups demonstrated a decrease in ALP activity when compared to CT at both periods of cell exposure. Conclusions: The hDPCs were suitable for the evaluation of new endodontic materials in vitro. MTAP may be considered a promising material for endodontic treatments.
Keywords: Dental pulp; Silicate cement; Cell viability; Alkaline phosphatase